KNOWLEDGE, ATTITUDE AND BARRIERS TO THE UTILIZATION OF EMERGENCY CONTRACEPTIVES AMONG FEMALE STUDENTS OF THE UNIVERSITY FOR DEVELOPMENT STUDIES: A CROSS-SECTIONAL STUDY - Shamsu-Deen, Z.; Sufyan, B. S.; Issah, F. (UDS International Journal of Development, 2022)
Unintended and unwanted pregnancy is a public health threat among young women and girls in developing countries including Ghana. Despite all the public health interventions, the effectiveness of the use of emergency contraceptives (ECs) to avert unintended pregnancies is still low in Ghana. Little is known about the knowledge, attitude, and barriers to ECs utilization in Ghana. Therefore, the objective of the study was to investigate the knowledge, attitudes, and barriers to the utilization of ECs among female students of the University for Development Studies, Tamale. A total of 309 female students of reproductive age were selected using a simple random approach. A descriptive cross-sectional study design was used for the study. Also, a semi-structured questionnaire was used to collect data on knowledge, attitudes, and barriers to the utilization of ECs. Frequency and percentage distribution of the sociodemographic factors, and behavioral and attitude variables of EC variables were computed using the SPSS software (version 20). Overall, the majority (65.0%) of the participants showed sufficient knowledge of ECs. Also, 54.0% of the respondents had a good attitude toward EC. An assessment of the reasons for not using any form of ECs revealed that some of them wanted pregnancy (26.6%), lacked knowledge about ECs (18.1%), and partner refusal (4.3%). Also, religious beliefs (37.2%) were barriers to the utilization of ECs. In conclusion, the study found a high level of knowledge and a good attitude toward ECs among the study participants. However, partner refusal and religious beliefs were mentioned as barriers to the utilization of ECs. Therefore, we recommend that the health authorities in charge of reproductive health education should liaise with religious leaders as they could partner in the creation of awareness of EC. Keywords: Emergency Contraceptive, Knowledge, Attitude, Barriers, utilization.